Effects of Propofol and Thiopental on Brain Relaxation and Hemodynamic Response to Craniotomy Supratentorial Tumors Removal - Valentino, Andrea; Wijaya, Wan Novriza; Anggraeni, Novita; Sony, Sony (Faculty of Medicine, Universitas Padjadjaran, 2025)
Surgical procedures for brain tumors, particularly supratentorial tumor removal via craniotomy, present challenges related to brain relaxation and maintaining hemodynamic stability. The choice of intravenous anesthetics, such as Propofol and Thiopental, is crucial due to their distinct effects on intracranial pressure (ICP), cerebral blood flow (CBF), and hemodynamic parameters. This study aimed to compare the effects of Propofol and Thiopental on brain relaxation and hemodynamic responses during supratentorial tumor removal. A randomized experimental study was conducted at Arifin Achmad General Hospital, Riau, Indonesia, from May to September 2024 involving patients undergoing elective craniotomy for supratentorial tumors. Patients were divided into two groups: the Propofol group (1-3 mg/kg body weight, with maintenance of 50-100 µg/kg/min) and the Thiopental group (4-6 mg/kg body weight, with maintenance of 100-200 µg/kg/min), both receiving continuous infusion until a bispectral index of 40-60 was achieved. Hemodynamic parameters, including systolic blood pressure, diastolic blood pressure, mean arterial pressure (MAP), and heart rate, were measured at various stages: before induction, during surgery, and at multiple intervals. Brain relaxation was subjectively assessed by a neurosurgeon using a four-point scale. Results showed that 90% of subjects receiving Thiopental experienced good brain relaxation during duramater opening, compared to 70% in the Propofol group, though this difference was not statistically significant (p=0.118). Hemodynamically, the Thiopental group exhibited higher diastolic blood pressure and MAP at induction (p<0.05). In conclusion, Thiopental demonstrated superior hemodynamic stability, albeit both agents provided equally effective brain relaxation.